Environmental and energy law : international dimensions - Viñuales, Jorge E., 1973-; Lees, Emma (International library of law and the environment ;, 2017)
This Research Review covers the main topics and dimensions of environmental and energy law in its contemporary expression. It discusses foundational material for those interested in understanding the development of the field and conducting research on the myriad of questions raised by transitions to sustainability. Particular emphasis is placed on the systematisation of the material. The Research Review discusses articles that cover international dimensions, including principles, substantive areas of regulation and implementation techniques as well as the European dimensions broadly understood, including EU law and other regional approaches (the UNECE) and distinguishing sector-specific and transversal regulation. It also looks at the transnational, comparative and domestic dimensions and major questions arising from selected English-speaking jurisdictions. Edited by two recognised experts in the field, this research review will provide a solid foundation for the study of environmental and energy law.